La pedagogia di Leopardi. Le fonti e l'influenza rousseauiana - Michele Zedda (Firenze University Press, 2017)
Leopardi's pedagogy contains other authors' influences, it is therefore necessary to deal with the problem of sources. Rousseau's works (Emil in particular) are very relevant to this kind of study. Leopardi and Rousseau consider some pedagogical questions from a similar point of view. It's the case of childhood, of educator, of experience, of criticism against official educative theories.